Determinants of CSR disclosure in Mexico. (5th April 2020) - Arena, Claudia; Petrides, Yanira; Vourvachis, Petros
This paper investigates corporate social (and environmental) responsibility (CSR) disclosure practices in Mexico. By analysing a sample of Mexican companies in 2010, it utilises a detailed manual content analysis and identifies corporate-governance-related determinants of CSR disclosure. The study shows a general association between the governance variables and both the content and the semantic properties of CSR information published by Mexican companies. Although an increased international influence on CSR disclosure is noted, the study reveals the symbolic role of CSR committees and the negative influence of foreign ownership on community disclosure, suggesting that improvements in business engagement with stakeholders are needed for CSR to be instrumental in business conduct.